PERSONALIZED TREATMENT OF OBSTRUCTIVE SLEEP APNEA: IS IT STILL A LONG WAY OFF? - Stamenković, Zoran; Ristic, Lidija; Pejcic, Tatjana; Jovanovic, Hristina; Trajkovic, Hristina; Bjelakovic, Marko; Cvetkovic, Jelena; Matejic, Ivan (Acta medicae Medianae, 2023)
The combination of sleep fragmentation, intermittent hypoxia exposure and circadian rhythm misalignment is crucial to represent multiple obstructive sleep apnea (OSA) clinical scenarios. Treatment of OSA has traditionally been directed to anatomical component treatment, implying the application of continuous positive airway pressure (CPAP) therapy, oral devices, upper airways surgery, weight loss, and positional therapy. These therapeutic approaches may be frustrating, especially in patients who fail to tolerate CPAP therapy, they may require personal engagement and are hardly maintained, or they have variable and hardly predictable efficacy. So, new treatment approaches aiming at specific, treatable, phenotype characteristics of OSA are needed as alternative therapeutic options.
Keywords: OSA phenotypes, personalized treatment of OSA